Preferensi Pegawai Negeri Sipil Kementerian Agama Tanjung Balai Dalam Memilih Pembiayaan Di Bank Syariah - Asra Idriyansyah Purba (JPS (Jurnal Perbankan Syariah), 2021)
This study aims to determine the influence of religion and economy on the preferences of civil servants in the Ministry of Religion of Tanjung Balai in choosing to finance in Islamic banks both partially and simultaneously. This research uses quantitative research methods, involving 63 people from various work units within the Ministry of Religion, Tanjung Balai. This study uses analytical techniques that emphasize hypothesis testing with test models and statistical tests. The results of this study indicate that partially the religious factor has no influence on the preferences of the Tanjung Balai Ministry of Religion civil servants in choosing to finance in Islamic banks. Meanwhile, economic factors have an influence on the preferences of the Tanjung Balai Ministry of Religion civil servants in choosing to finance in Islamic banks. Simultaneously, religious and economic factors have a positive influence on the preferences of the Tanjung Balai Ministry of Religion civil servants in choosing to finance in Islamic banks.